Excitation of helically-trapped-energetic-ion driven resistive interchange modes with intense deuterium beam injection and enhanced effect on beam ions/bulk plasmas of LHD. (29th June 2018) - Bando, T.; Ohdachi, S.; Isobe, M.; Suzuki, Y.; Toi, K.; Nagaoka, K.; Takahashi, H.; Seki, R.; Du, X.D.; Ogawa, K.; Ido, T.; Shimizu, A.; et al.
Abstract: Energetic ion driven resistive InterChange modes (EICs) accompanying repeated bursts of the magnetic fluctuations were found in hydrogen campaign of large helical device. The pressure gradient of helically trapped energetic particles, which are mainly produced by perpendicularly injected beams, drives this mode. Recently, perpendicular neutral beam injection (PERP-NBI) systems are upgraded for deuterium plasma campaign. The beam energies of the two PERP-NBIs are increased from 40/40 keV to 60/80 keV, respectively. And the injection powers increase from 6/6 MW to 9/9 MW, as well. As results of these upgrades of NBIs, the β value of helically trapped energetic ions, , has increased up to  ̃0.35% and induced EICs with larger bursts and smaller repetition frequencies. It is found that the threshold of to excite EICs increases with deuterium PERP-NBIs. The amplitude of each burst and effect on energetic beam ions become larger when is larger. In addition, a large electrostatic potential about  −25 kV is observed when EICs are excited, which is about two times larger than the potential observed in hydrogen campaign. The transient increases of the electron density and temperature in edge regions are clearly observed when the electrostatic potential is formed.